Peste no estado do Ceará (1900-2008) : epidemiologia, vigilância e ações de controle - Aragão, Antonia Ivoneida (2009)
Our objective was to describe, in a historical perspective, the epidemiological profile of plague in the State of Ceará since 1900 and the evolution of the activities of the disease control from 1980 to 2008. We carried out a descriptive study using an historical approach based on the oral history for the construction of epidemiological and operational scenarios and a review of the historical and epidemiological information about the plague control program. To strengthen the information obtained, we conducted interviews with experts in the area. Historical records of human cases have been recovered only from 1935, and periods of intense activity and others of quiescence were identified. It is noteworthy that in the years 1980 plague persisted as endemic in Serra da Ibiapaba until 1986. In the period from 1982 to 1985 there was an outbreak in Serra de Baturité with 89 confirmed human cases; a rise of the rodents’ population and significant increasing in the activities of the program were observed. In the 1990s, only three human cases were confirmed in Serra da Ibiapaba and in 2005 another case was confirmed in Serra da Pedra Branca. The decline of human cases after 1986 led to the reduction of the program activities. For several decades the activities of the Plague Control Program (PCP) included health education, active search for plague activity and collection of specimens for bacteriological and serological analysis. Serological surveys in domestic carnivores (dogs and cats) predators of rodents were introduced into the routine of PCP in 1989 to monitor Y. pestis activities in the foci proving the most effective tool to detect the zoonosis activities in the foci. In spite of the occurrence of positivity peaks detected in 1997, 2001 and 2005, this activity has been diminished in the state and the present recommendation is to restrict the serological surveys to canine samples only. The Ceará foci are located in the ecological complexes of the “serras” Baturité, Machado, Matas, Pedra Branca, Uruburetama, Ibiapaba and Araripe. The foci area were formerly dealt as ecological units; however after the political/administrative division of the areas, in view of the “decentralization process”, they are now scattered among the “Regionais”. The Ceará foci are among the most important in Brazil, both by the number of human cases and by evidence of the permanent circulation of the bacterium. The persistence of plague in the state should therefore be considered a real and permanent risk in these regions, which may extend to other places, including urban centers, making it imperative that health professionals are prepared. Therefore, to ensure the monitoring of the foci, it is essential to maintain surveillance under the ecological approach, to enable the adoption of appropriate control measures for protection of human populations in focal areas.